The development of a febrile response to pyrogen in the thyroid-deficient rabbit - Macari, Marcos [UNESP]; Pela, I. R.; Silva, C. A A (My University, 1987)
The development of the febrile response to E. coli lipopolysaccharide (1.5 μg/kg, i.v.) in thyroid-deficient rabbits has been studied. Twenty-eight New Zealand White rabbits weighing 2.1-2.3 kg were used. Hypothyroidism was induced by treatment with propylthiouracil (100 or 200 mg/kg body wt./15 days). Thyroid-deficient animals showed a reduction in the febrile response to lipopolysaccharide, but the effect was significantly different (p<0.01) from the control only for rabbits treated with 200 mg/kg of propylthiouracil. Propranolol (2 mg/kg, i.p.) given 30 min before lipopolysaccharide also reduced (p<0.01) the fever response in control rabbits. The results of this experiment are consistent with the hypothesis that the reduction in the febrile response of thyroid-deficient rabbits is due to the reduced number of β-adrenergic receptors, or to a change in the availability of neurotransmitter in thermogenically active tissues, such as brown fat.
Keywords: escherichia coli endotoxin; propranolol; propylthiouracil; animal experiment; central nervous system; dose time effect relation; drug inhibition; endocrine system; fever; hypothyroidism; intraperitoneal drug administration; intravenous drug administration; nonhuman; oral drug administration; pharmacokinetics; rabbit; therapy; thyroidectomy; Animal; Body Temperature; Fever; Hypothyroidism; Lipopolysaccharides; Male; Propranolol; Propylthiouracil; Pyrogens; Rabbits; Support, Non-U.S. Gov't